INQUISITION AND POLICE INQUIRY: Revisiting the Medieval Tribunal and the Modern Criminal Procedure through a Penal Abolitionist Lens (Reflection and Critique Law Magazine, 2026)
This article explores the historical continuities between the medieval inquisitorial system and Brazil’s contemporary police inquiry. Using a qualitative and bibliographical methodology, the research adopts an interdisciplinary lens to examine how medieval practices — such as secrecy, centralized authority, and confession-based truth — were developed by the Catholic Church and later adapted by the modern state. The Inquisition, originally created to suppress heresy and defend Christian unity, relied on secret procedures and unilateral power. These characteristics remain present in the police inquiry, which, though pre-trial in nature, often functions without full adversarial guarantees. The study argues that the inquisitorial model was not abandoned with modernity but reconfigured as a tool of social discipline. By drawing from legal, historical, and sociological perspectives, the article shows that the medieval inquisitor’s role survives today in the figure of the police investigator. In conclusion, the paper calls for legal and structural reforms that move away from punitive traditions and toward democratic and human rights-based justice.